The resettlement net: ‘revolving door’ imprisonment and carceral (re)circulation - Cracknell, Matt (Punishment & society, 2023)
The Offender Rehabilitation Act (ORA) 2014 has extended post-release supervision to all individuals serving short sentences in England and Wales – a cohort who previously faced neglect within the criminal justice system. This empirical study uses a case study approach to explore the resettlement experiences of individuals subject to this new legislation, understanding how individuals circulate and re-cycle between a range of services and agencies in the community, further illuminating upon the reality of repeat ‘revolving door’ imprisonment. Drawing upon Cohen's ‘net widening’ analogy, this article posits that collectively the array of services involved in an individual's resettlement form a ‘resettlement net’, which segregates individuals in the community through control and surveillance functions, extending the carceral boundary of the prison firmly into the community. Welfare-orientated organisations become compelled to ‘braid’ welfare responses alongside penal functions in order to operate within the resettlement net. This article also explores some of the difficulties that individuals experience as they navigate the resettlement net, including informal forms of exclusion, and the wear and tear of the net, which undermines the rhetoric of care envisioned by this legislation, and drives individuals deeper into the mesh of carceral control.